2009
DOI: 10.1101/lm.1509909
|View full text |Cite
|
Sign up to set email alerts
|

Older and stronger object memories are selectively destabilized by reactivation in the presence of new information

Abstract: Reactivation can destabilize previously consolidated memories, rendering them vulnerable to disruption and necessitating a process of reconsolidation in order for them to be maintained. This process of destabilization and reconsolidation has commonly been cited as a means by which established memories can be updated or modified. However, little direct evidence exists to support this view. The present study addressed this issue by analyzing the influence of novel salient information present at the time of memor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

20
104
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 119 publications
(126 citation statements)
references
References 58 publications
20
104
0
Order By: Relevance
“…There were no significant differences in any of the control measures analyzed (all P . 0.05), indicating that animals in all drug conditions showed similar general object exploration behavior in the sample, reactivation, and choice phases (means and SEMs were consistent with previously established values Winters et al 2009). Control measure values for each experiment are presented in Supplemental Table S1.…”
Section: Resultssupporting
confidence: 72%
See 4 more Smart Citations
“…There were no significant differences in any of the control measures analyzed (all P . 0.05), indicating that animals in all drug conditions showed similar general object exploration behavior in the sample, reactivation, and choice phases (means and SEMs were consistent with previously established values Winters et al 2009). Control measure values for each experiment are presented in Supplemental Table S1.…”
Section: Resultssupporting
confidence: 72%
“…For example, degradation of synaptic proteins via ubiquitin proteasome system (UPS) activation likely underlies the putative synaptic uncoupling of the memory trace that could enable various forms of potential memory modification during the destabilization period (e.g., erasure or weakening, updating, strengthening) (Lee 2008;Lee et al 2008;Choi et al 2010). Despite these advances, few studies have directly addressed the connection between memory destabilization and conditions favoring novel information encoding (Morris et al 2006;Winters et al 2009). Recently, however, Reichelt et al (2013) demonstrated the important role that dopaminergic transmission may play in relation to prediction error.…”
mentioning
confidence: 99%
See 3 more Smart Citations